Effect of irrigation scheduling and fertigation on storability of onion (Alliunt cepa) under microsprinkler irrigation regime - KUMAR, SATYENDRA; KUMAR, ASWWANI; MANDAL, GOUTAM (The Indian Journal of Agricultural Sciences, 2011)
The experiment was carried out for 2 consecutive years (2002-2003) in a semi-arid climatic to study the effect of variable irrigation and fertigation on storage behavior of onion (Alliurn cepa L.) On the basis of irrigation water applicd (I W) and cumulative an evaporation (CPE) ratio, crop was subjected to 4 levles of irrigation where IWICPE ratio varicd from 0.60 to 1.20 at 0.20 interval. In each irrigation, 10.80 nim water was applicd. By varying 111c cumulative pan evaporation, the desired irrigation level was maintained. Three fertigati onoptions ofNPK, viz F, (100:50:50 kg’haj, F, (75:37:5:37.5 kg/ ha) and F, (50:25:25 kgllla) were studied. The field cured onion bulbs were stored in 2 conditions, i e on-cemented floor in loose and kept on wooden stack above the ground in gunny bags. Irrigation and ferrtigation levels sinigifacantly influenrcd physiological loss i11 weight (Oh) (data) and sprouting percentage (data). The bulb grown under low soil nroisturc rcginle rcsultcd in higher physiological loss in weight (%) and sprouting. The maximum sprouting percentage (25.49%) atas rccordcd under irrigation regime of I, when bulb stored on cemented floor in loose whereas sprouting was higllcst (12.76%) under the irrigation regi uco f I, when bulb stored in gunny bags. The higher sprouting as wcll as pliysiological loss in weight was found in fcrtigation level F, in which maximum trients were applied amongst all fertigation treatment.